Effects of Microbial and Heavy Metal Contaminants on Environmental/Ecological Health and Revitalization of Coastal Ecosystems in Delaware Bay - Ozbay, Gulnihal; Chintapenta, Lathadevi K.; Cannon, Amy; Hannum, Kenneth (Frontiers in Environmental Science, 2017)
The presence of heavy metals, excess nutrients, and microbial contaminants in aquatic systems of coastal Delaware has become a public concern as human population increases and land development continues. Delaware's coastal lagoons have been subjected to problems commonly shared by other coastal Mid-Atlantic states: turbidity, sedimentation, eutrophication, periodic hypoxic/anoxic conditions, toxic substances, and high bacterial levels. The cumulative impact of pollutants from run-off and point sources has degraded water quality, reduced the diversity and abundance of various fish species, invertebrates, and submerged aquatic vegetation. The effects are especially pronounced within the manmade dead end canal systems. In this article, we present selected case studies conducted in the Delaware Inland Bays. Due to the ecological services provided by bivalves, our studies in Delaware Inland Bays are geared towards oysters with special focus on the microbial loads followed by the water quality assessments of the bay. The relationships between oysters (Crassostrea virginica), microbial loads and nutrient levels in the water were investigated. The heavy metal levels monitored near the waste water treatment plant in the inland bays are marginally higher than the recommended EPA limits Also, our studies confirmed that aerobic bacteria and Vibrionaceae levels are salinity dependent. Total bacteria in oysters increased when nitrate and total suspended solids increased in the waters. Studies such as these are important because every year millions of Americans consume raw oysters. Data collected over the last ten years from our studies may be used to build a predictive index of conditions that are favorable for the proliferation of human pathogenic bacteria. Results from this study will benefit the local community by helping them understand the importance of oyster aquaculture and safe consumption of oysters while making them appreciate their ecological and commercial values. This will also be of tremendous help to the commercial shellfish aquaculture farms to predict poor conditions to prevent oysters’ consumption when bacterial levels are high in water.